PWE-080 Prevalence of Faecal Incontinence in Adults with Inflammatory Bowel Disease. (4th June 2013) - Duncan, J; Sebepos-Rogers, G; Poole-Wilson, O; To, C; Canavan, J B; Ward, M; Kariyawasam, V; Goel, R; Patel, K; Stanton, A; Sastrillo, M; Anderson, S; et al.
Abstract : Introduction: The prevalence of faecal incontinence (FI) in people with inflammatory bowel disease (IBD) has not been fully explored. FI is not only associated with social stigma but also with decreased quality of life. In the general population prevalence is estimated at between 1–10%. Awareness of the prevalence of FI in IBD is important to aid management strategies and resource allocation. Methods Aim: To investigate the prevalence of FI in adults with IBD in a tertiary care setting. Methods: We performed a cross sectional questionnaire survey of 380 adults attending IBD outpatients at Guy's & St.Thomas' Hospitals. Patient surveys were: the validated International Consultation on Incontinence – Bowels (ICIQ-B) questionnaire, detailing frequency and severity of bowel pattern, control and quality of life; and the non-validated Bowel Leakage questionnaire, detailing any prior interventions by health care professionals. Demographics of age, gender, diagnosis, Montreal classification, St Mark's Continence Score and disease activity were also recorded. Data was entered into a database and analysed using a SPSS statistical package. Results: Median age was 38 years (IQR 31–50) and 180/380 (47%) were female. The mean duration of IBD diagnosis was 8.7 years (3.4–15.1). 151/380 (40%) had UC vs 229/380 (60%) CD. Overall, 255/380 (67%) reported FI as defined by any episode of uncontrolled bowel opening in the preceding three months, while 343/380 (90%) reported anal incontinence of flatus or faeces. Incontinence was strongly associated with disease activity, occurring during disease flares in 57% of people. However, 37% experienced incontinence both during relapse and remission, whilst only 5% experienced incontinence uniquely when in remission. The ICIQ-B control score was associated with current disease activity in CD (r = 0.29, p < 0.0001) but not in UC. There was no significant difference in FI prevalence between patients with Crohn's Disease (CD) or Ulcerative Colitis (UC), (66% vs 68%, p = 0.74). Conclusion: Faecal incontinence in IBD increases in proportion to disease activity. Given the availability of specialist FI interventions and support, we recommend that sensitive questioning regarding FI should be part of routine disease surveillance in the outpatient setting to cater for this unmet need. Disclosure of Interest: None Declared.